2015
DOI: 10.1007/s12010-015-1815-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Starvation Induced Changes in Root System Architecture, Carbon:Nitrogen Metabolism, and miRNA Expression in Nitrogen-Responsive Wheat Genotypes

Abstract: Improvement of nutrient use efficiency in cereal crops is highly essential not only to reduce the cost of cultivation but also to save the environmental pollution, reduce energy consumption for production of these chemical fertilizers, improve soil health, and ultimately help in mitigating climate change. In the present investigation, we have studied the morphological (with special emphasis on root system architecture) and biochemical responses (in terms of assay of the key enzymes involved in N assimilation) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 48 publications
3
59
0
1
Order By: Relevance
“…Further, this report also suggested that N-concentration and limited-N duration are inversely related with the expression of specific TaMIRs under investigation. A recent study performed under normal and limited nitrate conditions in two wheat genotypes (Sinha et al, 2015), detected a set of ten differentially expressed miRNAs in plant roots. Some notable differences among their expressions were depending on both the genotype and the level of N availability.…”
Section: Mirnas and Their Targets Under Low Nitrogenmentioning
confidence: 99%
“…Further, this report also suggested that N-concentration and limited-N duration are inversely related with the expression of specific TaMIRs under investigation. A recent study performed under normal and limited nitrate conditions in two wheat genotypes (Sinha et al, 2015), detected a set of ten differentially expressed miRNAs in plant roots. Some notable differences among their expressions were depending on both the genotype and the level of N availability.…”
Section: Mirnas and Their Targets Under Low Nitrogenmentioning
confidence: 99%
“…Nitrogen is an important plant nutrient used in the synthesis of several bio-products such as nucleic acids and proteins (Kraiser et al 2011; Sinha et al 2015). The nitrogen requirement of a plant is generally supplied through N-rich fertilizers where the nitrogen uptake efficiency is important (Abrol et al 2011).…”
Section: Mirnas Associated With Abiotic Stress Responses In the Tritimentioning
confidence: 99%
“…The nitrogen requirement of a plant is generally supplied through N-rich fertilizers where the nitrogen uptake efficiency is important (Abrol et al 2011). However, up to 60 % of applied fertilizer is lost to the environment resulting in economical loss and environmental pollution (Sinha et al 2015). The efficiency of nitrogen uptake and transport may vary depending on the plant species and genotype.…”
Section: Mirnas Associated With Abiotic Stress Responses In the Tritimentioning
confidence: 99%
See 2 more Smart Citations